Relationship between background characteristics and neighborhood satisfaction of Iranian homeowners in Kuala Lumpur, Malaysia - Fallahi, Bahare; Hashim, Ahmad Hariza; Abdul Rahim, Husniyah; Sabri, Mohamad Fazli (International Institute for Science, Technology & Education, 2015)
This study examined the relationship between background characteristics and neighborhood satisfaction of Iranian homeowners in Kuala Lumpur, Malaysia. Data was collected from 235 respondents using self-administered questionnaire. Pearson’s correlation analysis revealed number of income earner, monthly income first income earner, and total earned income earner, had positive significant relationship with neighborhood satisfaction of homeowners in the study area. However, there was no significant relationship between age, size of household, number of children, Tim owners have been in Malaysia, time owners been living in current house, price of the residential unit, and neighborhood satisfaction of the homeowners. Analysis of variance (ANOVA) showed that neighborhood satisfaction differed between level of income of the respondent, while neighborhood satisfaction did not differ between levels of education and level of price of residential unit. Independent t-test revealed that there was significant difference between sex and neighborhood satisfaction of the respondents. These relationships indicate that those who are female, higher income are more satisfied. It is recommended that policy makers and planning authorities should give more emphasis on the improvement of income households to enhance their neighborhood satisfaction.